In silico and in vitro identification of candidate SIRT1 activators from Indonesian medicinal plants compounds database. (December 2019) - Azminah, Azminah; Erlina, Linda; Radji, Maksum; Mun'im, Abdul; Syahdi, Rezi Riadhi; Yanuar, Arry
Graphical abstract: Highlights: Structure-based pharmacophores screening predicted that mulberrin as the potential candidate SIRT1 activator. Ligand-based pharmacophores screening predicted that gartanin, quinidine, and quinine are the likely candidates SIRT1 activator. The MM-GB(PB)SA calculations confirmed that mulberrin, gartanin, quinidine, and quinine showed activity at SIRT1 allosteric region. Mulberrin, gartanin, quinidine, and quinine have been proven by in vitro assay as SIRT1 activator candidates. Abstract: Sirtuin 1 (SIRT1) is a class III family of protein histone deacetylases involved in NAD + -dependent deacetylation reactions. It has been suggested that SIRT1 activators may have a protective role against type 2 diabetes, the aging process, and inflammation. This study aimed to explore and identify medicinal plant compounds from Indonesian Herbal Database (HerbalDB) that might potentially become a candidate for SIRT1 activators through a combination of in silico and in vitro methods. Two pharmacophore models were developed using co-crystalized ligands that allosterically bind with SIRT1 similar to the putative ligands used by SIRT1 activators. Then, these were used for the virtual screening of HerbalDB. The identified compounds were subjected to molecular docking and 50 ns molecular dynamics simulation. Molecular dynamics simulation was analyzed using MM-GB(PB)SA methods. The compounds identified by these methods were tested in an in vitro study using a SIRT-Glo™ luminescence assay. Virtual screening using structure-based pharmacophores predicted that mulberrin as the best candidate SIRT1 activator. Virtual screening using ligand-based pharmacophores predicted that gartanin, quinidine, and quinine to be the best candidates as SIRT1 activators. The molecular docking studies showed the important residues involved were Ile223 and Ile227 at the allosteric region. The MM-GB(PB)SA calculations confirmed that mulberrin, gartanin, quinidine, quinine showed activity at allosteric region and their EC50 in vitro values are 2.10; 1.79; 1.71; 1.14 μM, respectively. Based on in silico and in vitro study results, mulberin, gartanin, quinidine, and quinine had good activity as SIRT1 activators.